Exploring Green Libraries: Sustainable Practices, Challenges, and Prospects in the Global Context - Jain, Sonal; Kashyap, Vinay Singh; Jhamaria, Charu (Journal of Information and Knowledge, 2025)
This research investigates the evolution, implementation, and challenges of green libraries, focusing on sustainable practices in library design and operations. A mixed-methods approach that combines a comprehensive literature review of the work related to green libraries has been employed. The study examines both global and local green library trends, identifies implementation barriers, and proposes evidence-based strategies for enhancing sustainability within library systems. The findings reveal a pronounced disparity in green library adoption: while developed nations have extensively integrated green building practices and sustainable operations into their library systems, libraries in India—particularly those in urban centres—are in the early stages of adopting green initiatives. However, these institutions face many obstacles, including financial constraints, inadequate infrastructure, and limited policy frameworks supporting sustainable development. The study concludes by offering practical, context-specific recommendations designed to advance library sustainability initiatives. These recommendations align with the United Nations Sustainable Development Goals (SDGs), providing a framework for libraries to contribute meaningfully to global sustainability objectives while addressing local implementation challenges.